2016
DOI: 10.1080/10410236.2016.1214225
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Risk on the Oxytocin Receptor Gene (OXTR) Predicts Empathic Communication by Physician Assistant Students

Abstract: In the relationship between patients and health care providers, few communicative features are as significant as the providers' ability to express empathy. A robust empirical literature describes the importance of physician communication skills-particularly those that convey empathy-yet few studies have examined empathic communication by physician assistants, who provide primary care for an increasing number of Americans. The present study examines the empathic communication of physician assistant students in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…There is some evidence that patients appreciate PA communication in hospital encounters [13, 16, 18, 19]. However, there is lack of understanding about the process of PA-patient communication [20] and how this might influence satisfaction, particularly in the context of the acute hospital setting. This setting presents significant challenges to effective communication within clinician-patient encounters: their often brief duration; the absence of a prior relationship; and the likelihood that the acutely ill patient will have interacted with many different medical/surgical team staff members [21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that patients appreciate PA communication in hospital encounters [13, 16, 18, 19]. However, there is lack of understanding about the process of PA-patient communication [20] and how this might influence satisfaction, particularly in the context of the acute hospital setting. This setting presents significant challenges to effective communication within clinician-patient encounters: their often brief duration; the absence of a prior relationship; and the likelihood that the acutely ill patient will have interacted with many different medical/surgical team staff members [21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, affectionate communication in close relationships modulates cortisol reactivity to a laboratory stressor (Floyd et al, 2007b; see also Ditzen et al, 2007), and enacting affectionate communication after a stressor accelerates cortisol recovery (Floyd et al, 2007a). Floyd, Pauley, and Hesse (2010) showed that serum oxytocin is partly responsible for the stress-buffering effect of affectionate communication, and additional studies have connected affectionate communication to blood lipids (Floyd et al, 2009;Floyd, Mikkelson, Hesse, & Pauley, 2007); natural killer cell toxicity (Floyd et al, 2014); B cells, T cells, and immunoglobulins (Floyd, Ray, van Raalte, Stein, & Generous, 2018); disordered sleep (Floyd, 2016); and susceptibility to pain (Floyd, Generous, Clark, McLeod, & Simon, 2017).…”
Section: Affectionate Communication and Healthmentioning
confidence: 99%